PENGARUH AUDIT SUMBER DAYA MANUSIA TERHADAP KINERJA PADA PT. SANGGAR LAUT MANADO - Anwar, Putri Listia; Sumayku, Sontje; Pio, Riane Johnly (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. In Running an enterprise activity need to make an assessment (evaluation) of the implementation of programs that have been developed human resources in achieving overall corporate objectives to ensure that the functions of the human resources (HR) has been running and contributing to better achievement in the company's success. Therefore, companies require an audit to assess whether the management of the programs and activities of the HR function is in conformity with the effort in achieving corporate goals. This study aims to determine, describe and explain the Influence of Human Resource Audit on Employee Performance at PT. Sanggar Laut Manado. Variables examined in this study are the Human Resource Audit as Independent Variables and Employee Performance as a Dependent Variable. In this study involving all employees who are 40 employees as respondents. The data used in this study are primary data and secondary data obtained from the questionnaires and interviews. For Audit Human Resources on Employee Performance, the author uses descriptive quantitative method, Spearman rank correlation, coefficient of determination analysis, and test results is done manually and using SPSS. Based on the statistical analysis of the results are as follows: Hypothesis Testing results indicate that the Human Resource Audit influence on employee performance. of these findings it can be concluded that the study results were declared "Human Resource Audit Significant effect on Employee Performance at PT. Sanggar Laut Manado "acceptable.Keywords: Audit of Human Resources and Employee Performance